2015
DOI: 10.5194/angeo-33-1081-2015
|View full text |Cite
|
Sign up to set email alerts
|

Tropical upper tropospheric humidity variations due to potential vorticity intrusions

Abstract: Abstract. Four cases (March 2009, May 2009, April 2010 and February 2012 are presented in which the ERA-interim relative humidity (RH) shows consistent increase by more than 50 % in the upper troposphere (200-250 hPa) over tropics at the eastward side of the potential vorticity (PV) intrusion region. The increase in RH is confirmed with the spaceborne microwave limb sounder observations and radiosonde observations over Gadanki (13.5 • N, 79.2 • E) and is observed irrespective of whether the PV intrusions are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…Please note that the high PV and dry air have been observed intruding deep into the troposphere as low as 650 hPa (∼ 3.6 km), whereas the vertical structure of AIRS ozone has shown that the enhanced ozone intruded into the troposphere at ∼ 500 hPa. This difference in vertical scale of intrusion between ozone and PV parameters is most likely due to two reasons: (1) the local high PV value observed near ∼ 600 hPa is not a true stratospheric characterized intrusion but rather adiabatically produced high PV (e.g., Skerlak et al, 2015); (2) the relatively poor vertical resolution of AIRS ozone data may have limited the refined observation of the intrusions. From this figure, however, it is clear that stratospheric air (dry ozone-rich and high PV) intrusions have indeed occurred and were observed (at least intruded downward into ∼ 500 hPa).…”
Section: Associated Stratospheric Intrusionsmentioning
confidence: 99%
See 2 more Smart Citations
“…Please note that the high PV and dry air have been observed intruding deep into the troposphere as low as 650 hPa (∼ 3.6 km), whereas the vertical structure of AIRS ozone has shown that the enhanced ozone intruded into the troposphere at ∼ 500 hPa. This difference in vertical scale of intrusion between ozone and PV parameters is most likely due to two reasons: (1) the local high PV value observed near ∼ 600 hPa is not a true stratospheric characterized intrusion but rather adiabatically produced high PV (e.g., Skerlak et al, 2015); (2) the relatively poor vertical resolution of AIRS ozone data may have limited the refined observation of the intrusions. From this figure, however, it is clear that stratospheric air (dry ozone-rich and high PV) intrusions have indeed occurred and were observed (at least intruded downward into ∼ 500 hPa).…”
Section: Associated Stratospheric Intrusionsmentioning
confidence: 99%
“…Backward (forward) trajectories in given starting locations are capable to reproduce the sources (destinations) of the air parcel that will allow us to examine the intrusions of stratospheric origin in the troposphere (e.g., Elbern et al, 1997 (Rolph, 2003;Stein et al, 2016) is applied to calculate the backward and forward trajectories. The calculation method of the model is a hybrid between the Lagrangian approach and the Eulerian methodology.…”
Section: Hysplit Modelmentioning
confidence: 99%
See 1 more Smart Citation